Title- Genomic landscape of squamous cell carcinoma- Different genetic pathways culminating in a common phenotype. (2020) - Krishnamurthy, Kritika; Lindsey, Allison M; Estrada, Christie-Anne; Martinez, Camila C; Cusnir, Mike; Schwartz, Michael; Sriganeshan, Vathany; Poppiti, Robert
Highlights: - Squamous cell carcinomas are the most common solid tumors found across multiple organ systems. - Certain genes appear to be more frequently mutated in a given SqCC. - TP53 mutations were more frequent in pulmonary as compared to non-pulmonary sqccs. - NOTCH gene family and CREBBP mutations were limited to non-pulmonary SqCC . Abstract: Introduction: Squamous cell carcinomas (SqCCs) are the most common solid tumors in humans and are found across multiple organ systems. Although, integrated analysis of genetic alterations divulge similarities between SqCCs from various body sites, certain genes appear to be more frequently mutated in a given SqCC. These subtle differences may hold the key to determining the differentiation characteristics and predicting aggressiveness of tumors. Materials and Method: Fifty-four cases of SqCCs, in which the primary location of the tumor could be ascertained by clinical and radiological findings, were included in this study. Next generation sequencing data was analyzed for recurrent genetic abnormalities. Results: Genetic alterations were found in 219 genes in the 54 cases studied. TP53 mutations were found to be more frequent in pulmonary SqCCs (86.5%) as compared to non-pulmonary SqCCs (58.8%) ( p <0.05). NOTCH gene family mutations and CREBBP mutations were limited to non-pulmonary SqCC ( p <0.005) and were mutated in 41.2% and 17.6% cases. Conclusion: A detailed comparative analysis of the genetic alterations identified by sequencing identified higher frequency of TP53 mutations in lung SqCCs as compared to non-pulmonary SqCCs. NOTCH and CREBPP mutations were found to be absent in lung and head and neck SqCCs and more frequent in SqCCs from other locations.